Gini ratio analysis in North Buton Regency - Boni, Yohanes; Firihu, Muhammad Zamrun; Adam, H. Pasrun; Suraya, Rahmat Sewa (International research journal of management, IT and social sciences, 2021)
This research was carried out in North Buton Regency in 2020. The purpose of this study was to determine the income inequality of the community both between the Regency and the District and between the District and the District and the variables that cause income inequality in the North Buton Regency. The results of the Gini Ratio analysis show that the income distribution of the people of North Buton Regency is relatively unequal with a Gini coefficient value of 0.36. Districts with low-income inequality (a) West Kulisusu District with a Gini coefficient of 0.24 (b) and Bonegunu District with a Gini coefficient of 0.29. Having moderate-income inequality (a) Kulisusu sub-district with a Gini coefficient of 0.32. (b) Wakorumba sub-district with a Gini coefficient of 0.32 and (c) Kambowa District with a Gini coefficient of 0.37. Meanwhile, sub-districts that have high-income inequality (a) North Kulisusu sub-district have a Gini coefficient of 0.43. The main variables that cause income inequality in North Buton Regency are differences in natural resource potential, differences in community skills and work ethic, differences in ownership of production factors, differences in regional accessibility, differences in community livelihoods, and government and private investment.